Satrya Emas sebagai Pendukung Suksesnya Program Desa Maslahat di Kabupaten Pasuruan - Abdillah Mundir (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Pasuruan Regency has the potential to become a pre-eminent district. With the slogan Pasuruan Maslahat, a variety of innovative programs created as an effort to accelerate economic progress and reduce economic inequality. The empowerment of underdeveloped villages through the Maslahat Village Program and the SME empowerment program through the Satrya Emas Program is a clear proof of the efforts of the Regional Leaders to constantly innovate for the welfare of the people. A series of awards received by Pasuruan Regent as a proof of hard work of all parties as an appreciation for consistency in the empowerment of SMEs and Disadvantaged Villages based on local potential. Satrya Emas Program and Maslahat Village Program are typical Pemuruan Program of Pasuruan Regency that support each other and integrated to create Pasuruan Regency which is superior in global economic competition.Keyword: Satrya Emas Program, Maslahat Village Program